Progress on neuromodulation for treatment of essential tremor - GUO Song; ZHANG Hong⁃hao; LI Jian⁃yu; YANG An⁃chao (Chinese Journal of Contemporary Neurology and Neurosurgery)
Essential tremor (ET) is the most common movement disorder in clinical practice. Some patients' daily activities are affected because of the serious tremor. The current drug treatment for this disease is not effective, but the neuromodulation technique such as deep brain stimulation (DBS) is effective. This article provides a review of the latest developments in neuromodulation for the treatment of ET, including clinical trails on magnetic resonance⁃guided focused ultrasound (MRgFUS), directional⁃DBS and percept⁃DBS, as well as the optimal stimulation targets for DBS, in order to provide a reference for the treatment of ET.